The health impact of residential retreats: a systematic review - Dhevaksha Naidoo; Adrian Schembri; Marc Cohen (BMC, 2018)
Abstract Background Unhealthy lifestyles are a major factor in the development and exacerbation of many chronic diseases. Improving lifestyles though immersive residential experiences that promote healthy behaviours is a focus of the health retreat industry. This systematic review aims to identify and explore published studies on the health, wellbeing and economic impact of retreat experiences. Methods MEDLINE, CINAHL and PsychINFO databases were searched for residential retreat studies in English published prior to February 2017. Studies were included if they were written in English, involved an intervention program in a residential setting of one or more nights, and included before-and-after data related to the health of participants. Studies that did not meet the above criteria or contained only descriptive data from interviews or case studies were excluded. Results A total of 23 studies including eight randomised controlled trials, six non-randomised controlled trials and nine longitudinal cohort studies met the inclusion criteria. These studies included a total of 2592 participants from diverse geographical and demographic populations and a great heterogeneity of outcome measures, with seven studies examining objective outcomes such as blood pressure or biological makers of disease, and 16 studies examining subjective outcomes that mostly involved self-reported questionnaires on psychological and spiritual measures. All studies reported post-retreat health benefits ranging from immediately after to five-years post-retreat. Study populations varied widely and most studies had small sample sizes, poorly described methodology and little follow-up data, and no studies reported on health economic outcomes or adverse effects, making it difficult to make definite conclusions about specific conditions, safety or return on investment. Conclusions Health retreat experiences appear to have health benefits that include benefits for people with chronic diseases such as multiple sclerosis, various cancers, HIV/AIDS, heart conditions and mental health. Future research with larger numbers of subjects and longer follow-up periods are needed to investigate the health impact of different retreat experiences and the clinical populations most likely to benefit. Further studies are also needed to determine the economic benefits of retreat experiences for individuals, as well as for businesses, health insurers and policy makers.